Diseño de un sistema de costo "ABC" en la clínica veterinaria "DINO SUR" ubicada en la provincia de Pichincha, cantón Quito. - Latacunga Guishcashana, Tania Pamela (2020)
Today companies seek to be in constant economic and technological growth, so they require different methods of business development, in order to be in advantage into a competitive market. The present research work was carried out at the Veterinary Clinic "Dino Sur", located in Pichincha province, city Quito aimed at resolving the unknown of cost; the purpose of it is to design an ABC cost system with the aim of issuing real information and concise of the cost generated in each activity carried out in the company, in order to achieve better longterm decision making, and a competitive advantage within the market. The research is not experimental quantitative and is developed under a mixed approach, this type of research was adopted since the information collected is based on documentation provided by the company, in addition it has as its scope the methods: quantitative, inductive, deductive and analytical, where different techniques and instruments were applied such as the interview, survey and observation sheet allowing to know more about the object of study. To carry out the project and the design of the ABC system focused on the materials used, the time spent and the necessary personnel in each activity carried out by the veterinary clinic, managing to establish the actual cost to charge for the care received. By designing the ABC cost system and partially applying it, it was corroborated that the entity does not know the costs of each activity, establishing that in the area of Hospitalization there is a significant loss of 106.45%, however, the Cleaning area generates greater value to the company since it has a gain of 56.53%. Taking into account the values obtained by the system it is necessary that the Veterinary Clinic "Dino Sur" carried out an analysis regarding the loss that exists in the area of hospitalization since the line items that are charged don’t produce usefulness for the company.